Implementasi Tahfiz Qur’an Pada Ekstrakurikuler Madrasah Ibtidaiyah - Yusrizal, Yusrizal; Fitri, Alaida (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the implementation of the Qur'an memorization program as an extracurricular activity at SD Patria Al-Ittihadiyah and the challenges encountered in its implementation. The research approach used in this study is qualitative with a phenomenological method, which prioritizes an in-depth understanding of the subjective experiences of students, teachers, and school officials. The results of the study indicate that the Qur'an memorization program at SD Patria Al-Ittihadiyah is running well and has a positive impact on students, both academically, in terms of character, and in their understanding of religion. However, several challenges have emerged, such as time constraints, variations in student motivation, and limited teaching resources. Limited time and inconsistent motivation among students are the main obstacles to the smooth running of the program. Nevertheless, the program has succeeded in fostering discipline, boosting self-confidence, and deepening students' religious understanding. This study provides new insights for the development of Qur'an memorization programs in elementary schools and suggests improvements in time management, student motivation, and the utilization of teaching resources to achieve more optimal results.